Population Dynamics of Whitefly and Disease Incidence of Yellow Vein Mosaic Virus Disease in Okra - , Samir Pratap Singh; , S. K. Singh; , L. P. Awasthi; , Pankaj Kumar Ray; , Vinod Kumar Singh; , Pavan Shukla; , Ashutosh Singh; , Lalbabu Kumar (Archives of Current Research International, 2024)
Okra (Abelmoschus esculentus L.) belong to the Malvaceae family and an important vegetable crop widely cultivated in the Indian subcontinent. However, several factors influence okra crop as biotic and abiotic. Among the diseases affecting its cultivation, okra yellow vein mosaic disease (OYVM) belong to the family Geminiviridae and genus Begomovirus and transmitted by whitefly (Bemisia tabaci, Order: Hemiptera, Family: Aleyrodidae, is the one of the most destructive disease. Randomly selected five plants of each plot were observed for the population of whitefly at weekly interval starting with 20 days after sowing. First appearance of whitefly was recorded at 30th standard weekand rapid progress of whitefly population was recorded from 31th standard week to 37th and 38th standard week during both the years. The whitefly population with the minimum temperature and relative humidity showed non-significant positive correlation, whereas, maximum temperature and rainfall was non-significantly negative correlated during both the years. The whitefly population was non-significantly positive correlated with percent disease incidence of YVMV.